O esoterismo ocidental: a trajetória da Sociedade Brasileira de Eubiose e sua representação na cidade do Recife (1960-1986). - Bezerra, Rodrigo Silva da Costa (2024)
Between the years 1960 to 1986, a period that involved, according to researchers of Western Esotericism, the New Era, one of the ways that esoteric thought spread in Brazil was through newspapers. In the city of Recife/PE, it was common to see articles in the newspapers Diário de Pernambuco and Diário da Manhã talking about esoteric orders in the city, such as Rosicrucianism, Círculo Esoterico da Comunhão do Pensamento, Teosofia and Eubiose, as well as comments about famous esotericists , like Helena Blavatsky and Papus. So we can say that we have a very rich and explored scenario in what researcher Diego Chaves called an “Esoteric Recife”. In this sense, our research aims to analyze the trajectory of the Brazilian Society of Eubiosis and Western Esoterism and its representations in the city of Recife, with regard to the way in which the media referred to the Eubiotic Order and the curious aspects of esotericism and how the representations were treated, in addition to the dimension that the subject took to the general public. This project is theoretically based on authors and researchers on Western Esotericism and the New Era, such as Elaine Moura, Amurabi Pereira, Silas Guerriero, Diego Chaves, Magnólia Silva and José Guilherme Magnani, as well as prominent writers in the area such as Antoine Faivre and Wouter Hanegraaff, essential for understanding the subject.